2006
DOI: 10.1080/01913120500408018
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Ultrastructural Findings of Prognostic Impact in Craniopharyngiomas

Abstract: Craniopharyngioma is a slow-growing epithelial tumor with an unpredictable tendency to recur. To verify the reliability in predicting the clinical outcome, some morphological and immunohistochemical findings were analyzed in 37 primitive tumors and in 6 recurrences (one recurred twice). All the tumors were surgically excised and all recurrences exhibited an adamantinomatous pattern; mitotic rate was low (< 5 x 10 HPF) in both recurrent and in nonrecurrent tumors. Primary tumors showed a mean positivity of 1.7%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 28 publications
0
18
0
1
Order By: Relevance
“…2,13,51,[55][56][57] One functional study using a corneal angiogenesis assay revealed that recurrent ACP samples had a significantly higher angiogenic potential than nonrecurrent ACP, but less than glioblastoma multiforme or arteriovenous malformations. 51 Imatinib-loaded microspheres reduced neovascularization in this model, but the use of this or other antiangiogenic approaches in patients has not been reported in the literature.…”
Section: Molecular Biology Of Tumor-associated Angiogenesismentioning
confidence: 99%
“…2,13,51,[55][56][57] One functional study using a corneal angiogenesis assay revealed that recurrent ACP samples had a significantly higher angiogenic potential than nonrecurrent ACP, but less than glioblastoma multiforme or arteriovenous malformations. 51 Imatinib-loaded microspheres reduced neovascularization in this model, but the use of this or other antiangiogenic approaches in patients has not been reported in the literature.…”
Section: Molecular Biology Of Tumor-associated Angiogenesismentioning
confidence: 99%
“…In recent years, several reports have indicated the recurrence of craniopharyngioma may correlate with the angiogenesis [30][31][32]. It is possible that, like endothelial cells, activity of the vascular endothelial growth factor/ vascular endothelial growth factor receptor-2 system and platelet-derived growth factor receptor-alpha in craniopharyngioma may be linked to the increasing permeability of epithelial cells and cyst formation.…”
Section: Discussionmentioning
confidence: 96%
“…However, morphological differences are controversial as a prognostic factor [1], and selection of the area of interest in the pathological specimen is not standardized for such stratified and heterogeneous tissue [10,19]. Sub-classification and more accurate risk evaluation of this tumor are required.…”
Section: Discussionmentioning
confidence: 99%